Influence of the Deposition Parameters on the Properties of TiO2 Thin Films on Spherical Substrates - Covei Maria; Bogatu Cristina; Gheorghita Silvioara; Duta Anca; Stroescu Hermine; Nicolescu Madalina; Calderon-Moreno Jose; Atkinson Irina; Bratan Veronica; Gartner Mariuca (Materials, 2023)
Wastewater treatment targeting reuse may limit water scarcity. Photocatalysis is an advanced oxidation process that may be employed in the removal of traces of organic pollutants, where the material choice is important. Titanium dioxide (TiO2) is a highly efficient photocatalyst with good aqueous stability. TiO2 powder has a high surface area, thus allowing good pollutant adsorption, but it is difficult to filter for reuse. Thin films have a significantly lower surface area but are easier to regenerate and reuse. In this paper, we report on obtaining sol-gel TiO2 thin films on spherical beads (2 mm diameter) with high surface area and easy recovery from wastewater. The complex influence of the substrate morphology (etched up to 48 h in concentrated H2SO4), of the sol dilution with ethanol (1:0 or 1:1), and the number of layers (1 or 2) on the structure, morphology, chemical composition, and photocatalytic performance of the TiO2 thin films is investigated. Etching the substrate for 2 h in H2SO4 leads to uniform, smooth surfaces on which crystalline, homogeneous TiO2 thin films are grown. Films deposited using an undiluted sol are stable in water, with some surface reorganization of the TiO2 aggregates occurring, while the films obtained using diluted sol are partially washed out. By increasing the film thickness through the deposition of a second layer, the roughness increases (from similar to 50 nm to similar to 100 nm), but this increase is not high enough to promote higher adsorption or overall photocatalytic efficiency in methylene blue photodegradation (both about 40% after 8 h of UV-Vis irradiation at 55 W/m(2)). The most promising thin film, deposited on spherical bead substrates (etched for 2 h in H2SO4) using the undiluted sol, with one layer, is highly crystalline, uniform, water-stable, and proves to have good photocatalytic activity.
Keywords: TiO2 thin film; photocatalysis; glass bead substrate; sol-gel; dilution ratio; number of layers; morphology structure; stability